Anti-Müllerian Hormone Levels and Cardiometabolic Disturbances by Weight Status Among Men in the 1999 to 2004 National Health and Nutrition Examination Survey - Beydoun, Hind A (J Endocr Soc, 2019)
CONTEXT: Serum anti-Müllerian hormone level (AMH) and body mass index may be jointly associated with cardiometabolic risk. OBJECTIVES: Examine the contribution of AMH to cardiometabolic disturbances by weight status among US adult men. DESIGN: Cross-sectional analysis using data from the 1999 to 2004 waves of the National Health and Nutrition Examination Survey. SETTING: Multistage probability sampling of the noninstitutionalized US population. PARTICIPANTS: US men aged ≥18 years. Final analytic sample sizes ranged from 517 to 1063 participants. MAIN OUTCOME AND EXPOSURE MEASURES: Cardiometabolic disturbances (metabolic syndrome and its components, insulin resistance, diabetes, and chronic inflammation) and AMH were obtained from trained staff and nurses in a mobile examination center or during in-home visits. RESULTS: AMH was directly associated with insulin resistance among obese men [OR 1.08 (95% CI 1.00, 1.15); P = 0.046; N = 146], whereas AMH was inversely associated with waist circumference (WC) among obese men [OR 0.95 (95% CI 0.91, 0.99); P = 0.049; N = 146]. An inverse relationship was also observed between categorical AMH and diabetes status [medium vs low AMH; OR 0.19 (95% CI 0.043, 0.84); P = 0.030; N = 145] among obese men, with a strong inverse relationship also detected among overweight men [high vs low AMH; OR 0.011 (95% CI 0.0004, 0.27); P = 0.007; N = 193]. An inverse relationship between continuous AMH and diabetes [OR 0.75 (95% CI: 0.59, 0.93); P = 0.011; N = 193] was also detected among overweight men. CONCLUSIONS: AMH was associated with specific cardiometabolic risk factors, including WC, diabetes status, and insulin resistance, in overweight and obese US men.